Bordering Power: Reinterpreting Three First Cataract Inscriptions of King Merenra - Siegel, Oren; Hainline, Brendan; Nicolini, Serena; Gatto, Maria Carmela (Études et Travaux, 2024)
This paper reconsiders three royal inscriptions of King Merenra (Sixth Dynasty) in the region of the First Nile Cataract. They have long been known to scholars but have not received extensive treatment beyond translations. The inscriptions appear to be among the first explicit royal statements addressing the limits of Egyptian territory and the beginnings of foreign lands. The paper situates the inscriptions within more comprehensive scholarship related to border studies, the geographic setting of the First Cataract region, and the historical context of the late Old Kingdom. We argue these inscriptions provide key information about political border-making during this period.